Under the moon - Akinyemi, Rowena (Oxford Univ. Press, 1995)
It is the year 2522, and the planet Earth is dying. The Artificial Ozone Layer is only 300 years old, but it is breaking up fast. Now the sun is burning down on Earth with a white fire. There is no water. Without water, nothing can live. Trees die, plants die, animals die, people die...In the colony under moon, people wait for news - news from home, news from the planet Earth. And in a spaceship high above Earth, a young man watches numbers on a computer screen. The numbers tell a story, and the young man is afraid. The planet Earth is burning, burning, burning...